High sensitivity Love-mode liquid density sensors - Turton, A.C.; Bhattacharyya, D.; Wood, D. (Sensors and actuators. A. Physical., 2005)
An experimental study into Love-mode liquid sensors using polyimide for a waveguide layer has been carried out. Love devices were built on Y-ST quartz with 40 μm wavelength inter-digitated transducers operating up to 124.7 MHz, and polyimide layers between 0.65 and 1.5 μm thick. The optimum polyimide thickness was 0.85 μm exhibiting a minimum insertion loss of 16 dB. Surface corrugations from 2.5 μm wide and 0.5 μm deep were etched in the polyimide to discriminate the liquid density from the square root of the density–viscosity product. A maximum sensitivity of up to 0.36 μg cm −3 Hz −1 has been obtained, a higher value than found in most other studies.